IMPLEMENTASI KESEHATAN DAN KESELAMATAN KERJA DI STASIUN LISTRIK PG JATITUJUH - Riyanto, Dede; Milana, Lia (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
In the current era of globalization, the industrial sector has undergone rapid and significant development. This progress encourages companies to improve productivity, product quality, and operational efficiency. However, such advancements are often accompanied by the use of modern technology, hazardous materials, and complex work processes, which inevitably increase the potential for workplace accidents if not properly managed. The larger the scale of an industry, the more complex the potential hazards become, thus elevating the level of risk. Occupational Safety and Health (OSH) is a critical aspect that must be prioritized to protect all workers within the workplace environment. Despite its importance, the implementation of OSH practices remains inadequate in many institutions. This lack of attention has led to numerous workers failing to apply safety protocols for their own protection. Furthermore, the use of Personal Protective Equipment (PPE) is essential in mitigating occupational hazards and plays a significant role in ensuring workplace safety and health (Ramli, 2010). Unfortunately, the level of worker compliance with PPE usage is still relatively low, which consequently increases the risk of accidents and injuries. Given these conditions, the implementation of OSH and proper PPE usage is urgently needed at PG. Jatitujuh. The nature of work activities and the production materials used at this facility present considerable opportunities for hazards and risks that could potentially endanger not only the workers within the plant but also the surrounding community.